PERANCANGAN SISTEM INFORMASI PENGELOLAAN MATA PELAJARAN MENGGABUNGKAN AUDIO KE DALAM SAJIAN MULTIMEDIA DI SMK NEGERI 5 SIJUNJUNG - Dhea Fauzia Putri (JURTEII: Jurnal Teknologi Informasi, 2021)
Management interpreted by as an work network or effort done by a group of people to with refer to activity in reaching specific purpose. Conducted management in study cover preparation of study, execution of study and also assessment of efficacy of study. Target of this research that is to yield Information System Management Of Subject Join Audio Into Form of Multimedia in SMK Negeri 5 Sijunjung. Research model in scheme of information system management of this subject use concept of System Development Life Cycle (SDLC) have 4 step in forming of information system that is planning, analyse, implementation and scheme. Scheme of analysis appliance and system use information system stream (ASI), for the scheme of system use HIPO, Context Diagram, Data of Flow Diagram, Entity Relationship Diagram. Result of information systems analysis management of subject join audio into multimedia expected to be sexpected by this system can walk and assist in course of learning and teaching, like appliance assist in submitting student and items can study items self-supportingly. Available and also of facility of interaktif to facilitate student in course of study. Result and solution in the form of existence of input process, process process and processing of output to woke up system. Input process by 7 entri form that is student data entri, teacher data entri, data entri of matpel, schedule entri and attendance data, items data entri and of entri value. Data processing which in input of processed and kept in a database. Process output present data which have been processed into a website. So that can yield an information system management of subject join audio Into Form of multimedia in SMK Negeri 5 sijunjung.